Cohabitation of Piscirickettsia salmonis genogroups (LF-89 and EM-90): synergistic effect on growth dynamics - Carril, Gabriela; Winther-Larsen, Hanne C.; Løvoll, Marie; Sørum, Henning (Frontiers in Cellular and Infection Microbiology, 2023)
Piscirickettsia salmonis, the biological agent of SRS (Salmon Rickettsial Septicemia), is a facultative intracellular bacterium that can be divided into two genogroups (LF-89 and EM-90) with different virulence levels and patterns. There are studies that have found co-infection of these genogroups in salmonid farms in Chile, but it is essential to assess whether this competitive interaction within the host is related to virulence and changes in pathogen dynamics. In this work, we studied four isolates from EM-90 and one LF-89 isolate chosen by their genomics differences. The aim was to evaluate how the co-cultures could affect the bacterial growth performance and virulence factors expression at in vitro and at in vivo cultures in Atlantic salmon (Salmo salar). In vitro results using FN2 medium, showed a similar growth curve between co-cultures of LF-89 with EM-90, compared to EM-90 monocultures. This was explained due to a higher ratio of EM-90 over LF-89 during all co-cultures. When evaluating the expression of virulence factors, it was discovered that the luxR gene was expressed only in EM-90-like isolates and that there were significant differences between mono-and co-cultures for flaA and cheA, suggesting a response to the cohabitation. Moreover, during in vivo cocultures, a transcriptomic analysis revealed an upregulation of transposases, flagellum-related genes (fliI and flgK), transporters and permeases that could unveil novel virulence effectors used in the early infection process of P. salmonis. Thus, our work has shown that the cohabitation of the genogroups of P. salmonis can modulate their behavior and virulence effectors expression. These data can contribute to new strategies and approaches to improve current health treatments against this salmonid pathogen.